2012
DOI: 10.3390/molecules170911056
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of the Essential Oils from Duguetia lanceolata St. Hil. Barks

Abstract: Essential oils of Duguetia lanceolata barks, obtained at 2 (T2) and 4 h (T4), were identified by gas chromatography and gas chromatography/mass spectrometry. β-Elemene (12.7 and 14.9%), caryophyllene oxide (12.4 and 10.7%) and β-selinene (8.4 and 10.4%) were the most abundant components in T2 and T4, respectively. The essential oils inhibited the growth of Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli and Candida albicans. The essential oils were cytotoxic against brine shrimp. The extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 20 publications
4
33
0
1
Order By: Relevance
“…One previous chemical study on the essential oil obtained from D. lanceolata barks performed by our research group revealed that the major components were sesquiterpenes, -elemene, caryophyllene oxide, selinene, -eudesmol and humulene epoxide II using GC/MS (Sousa et al, 2012). In the present study, 37 compounds were identified, which accounts for 92.7% of the total oil content with the presence of mono-and sesquiterpenes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…One previous chemical study on the essential oil obtained from D. lanceolata barks performed by our research group revealed that the major components were sesquiterpenes, -elemene, caryophyllene oxide, selinene, -eudesmol and humulene epoxide II using GC/MS (Sousa et al, 2012). In the present study, 37 compounds were identified, which accounts for 92.7% of the total oil content with the presence of mono-and sesquiterpenes.…”
Section: Discussionsupporting
confidence: 56%
“…This plant has been used as traditional medicine for various purposes such as anti-inflammatory, cicatrizing, analgesic, sedative and antimicrobial (Sousa et al, 2004(Sousa et al, , 2008. From the chemical point of view, -elemene, caryophyllene oxide, -selinene, -eudesmol and humulene epoxide II are the most concentrated components in the essential oil from barks and this oil has antimicrobial and cytotoxic properties (Sousa et al, 2012). In addition, the alkaloidal fraction produced a yield of 0.34% (Fischer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S. epidermidis) (Santos et al 2008). In addition, the bark essential oils of Duguetia lanceolata, where b-selinene is one of the most abundant components, showed activity against several microorganisms, including the gram-positive bacteria S. aureus and Streptococcus pyogenes (Sousa et al 2012).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Published studies have investigated the antiprotozoal and antibacterial activities of fixed and volatile constituents of species belonging to the Annonaceae family, e. g., B. multiflora , B. pleiosperma , D. lanceolata , G. australis , G. ferruginea , G. latifolia , G. sellowiana , G. friesiana , and G. pogonopus …”
Section: Introductionmentioning
confidence: 99%